BIOELECTROCHEMICAL TREATMENT MECHANISMS OF PETROLUME REFINERY WASTEWATER IN INTEGRATED SYSTEM OF MICROBIAL FUEL CELL-CONSTRUCTED WETLAND - & Ismail, Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Three identically designed systems named designate as MFC-CW, CW1,and CW2 were constructed and setup in this study for simultaneous biotreatment of real petroleum refinery wastewater (PRW) and bioelectricity generation. The three systems were planted with emergent wetland plant of Canna indica. These systems were operated simultaneously in a single batch mode to identify the dominant mechanism for organics removal from PRW. The operation period for each cycle was 8 days. Results demonstrated that maximum removal efficiency of the organic content represented as chemical oxygen demand (COD) were 96.5%, 89.3%, and 91% observed in MFC-CW, CW1, and CW2, respectively, whereby, the highest power generated in MFC-CW only was 12.36 mW/m2. The potential convergence of the results in the three systems indicated that the dominant mechanism of organic content removal from PRW was via bioelectrochemical reactions by the anodic biofilm in the MFC.